Proyecto de negocio internacional para la exportacion de seta shiitake fresca desde chipaque Cundinamarca a Londres Inglaterra - Lopez Pardo, Javier Leonardo (Universidad Antonio Nariño, 2022)
Despite the comparative advantages that Colombia has with respect to the productive factor of the land, the agricultural sector has not achieved the development that it should. The land problem has been the main cause as well as the opportunities for farmers and the lack of investment in technology.